Firm Dynamics, Productivity Growth, and Job Creation in Developing Countries : The Role of Micro- and Small Enterprises - Li, Yue; Rama, Martín (Oxford University Press on behalf of the World Bank, 2016)
The conventional wisdom on firm dynamics, productivity growth, and job creation in developing countries is based on data that, by design, excludes a vast number of micro- and small enterprises, many of which are informal. Some may not view this exclusion as an issue, on the grounds that the omitted economic units reflect survivorship rather than entrepreneurship. However, the thresholds that determine the truncation of the data are relatively arbitrary, and the firms that are typically excluded are associated with a large share of total employment. This paper assesses the ways in which the conventional wisdom on developing countries would change if micro- and small enterprises were taken into account in the analyses. The assessment shows that micro- and small enterprises account for a greater share of gross job creation and destruction than acknowledged by the conventional wisdom. It also reveals a greater dispersion of firm productivity, a weaker correlation between firm productivity and firm size, and a smaller contribution of within-firm productivity gains to aggregate productivity growth. This assessment points to new directions in the data and research efforts needed to understand the role of micro- and small enterprises and to identify policies with the potential to foster job creation and aggregate productivity growth in developing countries.